Preparation and Characterization of Microporous Cellulose Membranes as Potential Pathogen Filters - William, Joshua C.; Alexander, Tausi H.; Nambela, Lutamyo; Haule, Liberato V.; Ndazi, Bwire S.; Bulemo, Peresi M. (Tanzania Journal of Engineering and Technology, 2025)
Growth and development in the textile and fashion industry have resulted in the generation of large amounts of industrial pre-consumer textile wastes. It is estimated that 10 to 20% of textile fabrics are wasted during garment manufacturing, with most of the wastes being burned or landfilled. Reusing pre-consumer fabric wastes is therefore considered a viable approach to alleviate environmental impacts associated with their disposal. To achieve a higher porosity membrane, pre-consumer cotton fabrics were partially dissolved in a solution of dimethyl acetamide (DMAc) and lithium chloride (LiCl), and the resulting fibre suspension was utilized to prepare a microporous cellulose membrane (MCM) through a vacuum filtration method. The suspension comprised a mixture of partially and completely dissolved fibres, which provided the required morphological and structural integrity to the fibrous membranes. The membranes’ chemical structure, fibre size, and morphology were characterized based on Fourier transform infrared spectroscopy (FT-IR), light microscope, and field emission scanning electron microscopy (FE-SEM), respectively. The filtration efficiency of the microporous cellulose membranes was evaluated against 500 ppm sodium chloride (NaCl) solutions. The results showed that the filtration efficiency of the membranes ranged between 31.82 and 59.85% for cellulose membranes with 60.2% porosity, suggesting that the membranes could be applied as filters against pathogens upon further improvement.